Juridical Analysis Of Court Determination Number: 1/Pdt. P-Kons/2021/Pn Gpr On Consignment Land Acquisition At Dhoho Kediri International Airport - Isnaeni, Diyan; Sunardi, Sunardi; Nurdaiman, Taqiy (Universitas Islam Malang, 2025)
Abstract: In the implementation of the Deliberation on the Form and/or Amount of Compensation in the Land Procurement of Dhoho Kediri International Airport, there are Rights Holders who disagree with the deliberations, the Rights Holders who disagree do not submit an Objection to the local District Court, until finally the Land Procurement Implementer makes an Application for Compensation Custody through the Court. The validity of the Compensation Custody through the Court is reviewed from Law Number 2 of 2012, as well as what are the legal consequences of the issuance of the Court Determination. This research uses a normative juridical method, which analyzes a legal problem using laws, books, journals, and other written works that have legal standing. The conclusion of this study is that the Court accepted the Consignment Application because the Right Holder who did not agree with the results of the deliberation on the amount of compensation did not file an objection to the District Court 14 days from the holding of the Deliberation on the Form and/or Amount of Compensation Agreement, and its existence could not be found. The validity is absolute, considering that the conditions of the Application have been fulfilled by the Land Acquisition Implementer. Regarding the legal consequences of the Court Determination, it is considered to be the termination of the legal relationship between the Right Holder and its land, it is considered to be handing over the right to its land to the State, and the nature of the Determination is final so it must be accepted and implemented by all parties. In the end, the Right Holder accepted the results of the Consignment and was also present in the execution of the object in question.